MEMBANGUN KREATIVITAS PEMBELAJARAN GURU PENDIDIKAN AGAMA ISLAM MASA COVID-19 MELALUI CYBERSPACE LEARNING MODEL DI SMK NEGERI 1 SINGOSARI - Weny Tri Utaminingsih; Maskuri Bakri; Eko Setiawan (VICRATINA, 2021)
Critical thinking and generating creative ideas with the emergence of innovation is one of the ideas to be competent and develop in the era of globalization. Especially in the era of covid-19 where learning has been carried out online by utilizing technology or mass media (Cyberspace Learning Model). this is a new challenge for teachers at SMK Negeri 1 Singosari. Creativity plays an important and active role in learning because a creative teacher will be able to design lessons, create learning methods, utilize media and manage classes. The focus of the research includes the planning carried out by the teacher, the creativity of the teacher's learning, and the learning process through the Cyberspace Learning Model. This research was conducted using a qualitative research type with a descriptive approach. The findings obtained by the researcher are that the teachers of SMK Negeri 1 Singosari before carrying out learning must have the power of imagination and innovation so that they can utilize many learning media, can design learning well so that the learning process can occur according to the objectives.